La «prova glorificante»: Paradiso XXXIII - Güntert, Georges (Cuadernos de Filología Italiana, 2002)
In his reading of Paradiso XXXIII, Georges Güntert emphasises the semiotic correspondence of the mystical vision and the glorifying test that leads to the final acknowledgement of the hero. It is through this final sanction that Dante legitimises his own poetic mission. However, even within this experience of the transcendent, a clear distinction has to be made between the figure of the visionary hero (past and present), that of the narrator and the text itself. – An important aspect on the level of discourse (i.e. that of the text) is represented by the numerical configuration of this canto. Its first part consists of 45 verses entirely occupied by Saint Bernard’s prayer to the Virgin and is dominated by Beatrice’s number 9 (nine tercets). The whole canto counts 145 verses (45+100) and its second part is marked by the divine number 10 (33 tercets + 1 verse). The canto’s climax («Un punto solo m’è maggior letargo...») is particularly meaningful: a close analysis of this verse shows that the concept of admiratio is at the heart of it.